Extracellular Vesicles in Multiple Sclerosis: What are They Telling Us? - Sáenz-Cuesta, Matías; Osorio-Querejeta, Iñaki; Otaegui, David (Frontiers in Cellular Neuroscience, 2014)
Extracellular vesicles (EVs) are membrane-bound particles secreted by almost all cell types. They are classified depending on their biogenesis and size into exosomes and microvesicles or according to their cell origin. EVs play a role in cell-to-cell communication, including contact-free cell synapsis, carrying active membrane proteins, lipids, and genetic material both inside the particle and on their surface. They have been related to several physiological and pathological conditions. In particular, increasing concentrations of EVs have been found in many autoimmune diseases including multiple sclerosis (MS). MS is a central nervous system demyelinating disease characterized by relapsing of symptoms followed by periods of remission. Close interaction between endothelial cells, leukocytes, monocytes and cells from central nervous system is crucial for the development of MS. This review summarizes the pathological role of EVs in MS and the relationship of EVs with clinical characteristics, therapy and biomarkers of the disease.